Fabrication and characterization of MWCNT/natural Azerbaijani bentonite electroconductive ceramic composites. (November 2019) - Huseynov, Asgar; Israfilov, Aydin; Mammadova, Samira; Abdullayeva, Sevda; Sokolov, Sergey; Goryunkov, Alexey; Guliyev, Akif
Multi-walled carbon nanotubes have been synthesized by Aerosol-Chemical Vapor Deposition method. Carbon nanotubes firstly have been used as filler in affordable and prevalent natural Azerbaijani bentonite clays for fabrication electroconductive ceramic composites. In this paper, multi-walled carbon nanotubes/natural Azerbaijani bentonite ceramic composites were prepared by two-factor mechanical method and followed by calcination at 1050℃ in an inert atmosphere. The ceramic composites were characterized by scanning electron microscope, atomic force microscope, X-ray diffraction and thermogravimetric-differential-thermal analysis. X-ray diffraction analysis confirmed the presence of two principal components – multi-walled carbon nanotube and bentonite in composites. From the thermogravimetric-differential-thermal data, it was revealed that multi-walled carbon nanotube/ bentonite ceramic composites demonstrate thermo-oxidative stability up to 580–640℃. Scanning electron microscope images demonstrated a sufficiently high dispersibility of carbon nanotubes and satisfactory homogeneity in the composites. Experimental results demonstrated that by increasing the mass fraction of multi-walled carbon nanotubes from 1% to 8% in multi-walled carbon nanotube/bentonite ceramic composites, the electrical conductivity enhances substantially. The enhancement of electrical conductivity of the composites explained the mass fraction of multi-walled carbon nanotubes, as well as the uniform dispersion of multi-walled carbon nanotubes in the bentonite clays. Compared with other 8% multi-walled carbon nanotubes/bentonite ceramic composites, the electrical conductivity of heptane-multi-walled carbon nanotube/Gobu bentonite (σ = 397 S·m − 1 ) and heptane-multi-walled carbon nanotubes/Atyali (σ = 305 S·m − 1 ) composites is 2–5 times higher than the conductivity of composites obtained with cyclohexane carbon nanotubes- cyclohexane-multi-walled carbon nanotube/Atyali (σ = 78 S·m − 1 ), cyclohexane-multi-walled carbon nanotube/Gobu (σ = 111, 5 S·m − 1 ). These results can be explained with the structure, the number of layers, purity and diameter distribution, as well as the type and amount of defects in internal and external layers of Hep-multi-walled carbon nanotubes which cause better dispersion in bentonite clays. Due to the high conductivity and high temperature stability, these composites can be used as promising material for fabrication heating elements, electrodes, substrates for microelectronic devices, etc.